2014
DOI: 10.1364/boe.5.002301
|View full text |Cite
|
Sign up to set email alerts
|

Non-contact small animal fluorescence imaging system for simultaneous multi-directional angular-dependent data acquisition

Abstract: Abstract:We present a novel non-contact small animal fluorescent molecular tomography (FMT) imaging system. At the heart of the system is a new mirror-based imaging head that was designed to provide 360-degree measurement data from an entire animal surface in one step. This imaging head consists of two conical mirrors, which considerably reduce multiple back reflections between the animal and mirror surfaces. These back reflections are common in existing mirror-based imaging heads and tend to degrade the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…An in-depth broad review of commercial scanners has been provided by Leblond et al [23]. Regarding research prototypes, most acquire CW data [52][53][54][55][56][57][58][59][60] and a few are FD systems [56,[61][62][63][64]. Interestingly, a study comparing CW and FD systems and image reconstruction suggested that FD measurements may result in superior images but at much higher costs and efforts as regards instrumentation and computational resources [65].…”
Section: Journal Of Spectroscopymentioning
confidence: 99%
“…An in-depth broad review of commercial scanners has been provided by Leblond et al [23]. Regarding research prototypes, most acquire CW data [52][53][54][55][56][57][58][59][60] and a few are FD systems [56,[61][62][63][64]. Interestingly, a study comparing CW and FD systems and image reconstruction suggested that FD measurements may result in superior images but at much higher costs and efforts as regards instrumentation and computational resources [65].…”
Section: Journal Of Spectroscopymentioning
confidence: 99%
“…However, due to the strong scattering nature of optical photons in deep tissues and a limited number of measurements, the inverse problem of FMT is ill-posed and underdetermined, which results in low spatial resolution in FMT imaging, in particular for targets in deep turbid media. 2 Many approaches have been proposed to improve the FMT image quality, including multispectral wavelengths for both excitation and emission wavelengths, different illumination patterns, 12,13 a large number of FMT measurements by using charge-coupled device(CCD) cameras, [14][15][16][17][18] and improved FMT reconstruction algorithms--especially the sparse enhancement FMT reconstruction for the sparse FMT targets [19][20][21][22][23][24] . A region reconstruction method implemented with level set method was also introduced to improve the FMT image reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…For reflection mode, laser excitation and measurements are performed at the same side, 7 and it also lacks the information on the opposite side. Recently scholars have developed whole surface measurement FMT imaging systems 1,8,9 , in order to detect emission photons at most possible positions. The whole surface measurement mode can obtain more measurements than the half surface measurement modes, however, it might suffer from dynamic range problem.…”
Section: Introductionmentioning
confidence: 99%